2017
DOI: 10.1016/j.xphs.2017.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Application of Quantitative Targeted Absolute Proteomics to Profile Protein Expression Changes of Hepatic Transporters and Metabolizing Enzymes During Cholic Acid-Promoted Liver Regeneration

Abstract: Preoperative administration of cholic acid (CA) may be an option to increase the liver volume before elective liver resection surgery, so it is important to understand its effects on liver functionality for drug transport and metabolism. The purpose of this study is to clarify the absolute protein expression dynamics of transporters and metabolizing enzymes in the liver of mice fed with CA-containing diet for 5 days (CA1) and mice fed with CA-containing diet for 5 days followed by diet without CA for 7 days (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…As shown in Supplemental Fig. 4, the expression levels of transporters normalized by the level of 4f2 cellsurface antigen heavy chain, which showed homogenous protein expression in the PP and PC vein regions in the present study, are consistent with those obtained in plasma membrane fractions of total mouse liver (Miura et al, 2017) within differences of less than 2-fold, except for Oatp1a1, bile salt export pump, and Abcb4. This result suggests that the amounts determined with LMD-generated samples are broadly consistent with those obtained using wet liver tissues.…”
Section: Downloaded Fromsupporting
confidence: 90%
See 1 more Smart Citation
“…As shown in Supplemental Fig. 4, the expression levels of transporters normalized by the level of 4f2 cellsurface antigen heavy chain, which showed homogenous protein expression in the PP and PC vein regions in the present study, are consistent with those obtained in plasma membrane fractions of total mouse liver (Miura et al, 2017) within differences of less than 2-fold, except for Oatp1a1, bile salt export pump, and Abcb4. This result suggests that the amounts determined with LMD-generated samples are broadly consistent with those obtained using wet liver tissues.…”
Section: Downloaded Fromsupporting
confidence: 90%
“…The protein expression levels were determined as the amounts of trypsin-generated specific target peptides whose sequences had been selected based on in silico selection criteria (Kamiie et al, 2008). The SRM/multiple reactions monitoring transitions for the quantification of each peptide were set as reported previously (Miura et al, 2017) and are shown in Supplemental Table 1. The microdissected tissues were dissolved in denaturing buffer [7 M guanidium hydrochloride, 500 mM Tris-HCl (pH 8.5), 10 mM EDTA], and the proteins were S-carbamoylmethylated.…”
Section: Methodsmentioning
confidence: 99%
“…CA, CDCA, and TCA have also been reported to have roles in liver disease progression. Mice fed with a CA-containing diet for 5 days showed increased liver weight, cell proliferation index, and oxidative stress, (41) all of which resulted in enhanced visceral adiposity, atherosclerosis, and fatty liver disease. (42) TCA is an active promoter of the progression of liver cirrhosis through activating hepatic stellate cells through up-regulating toll-like receptor 4 expression.…”
Section: Discussionmentioning
confidence: 99%
“…However, mRNA expressions were correlated poorly with protein expressions for many DMEs [10,70]. Several recent studies applied targeted proteomics techniques to determine the changes in DMET protein expressions in response to different inducers, including antibiotics [71], rifampicin [72], corticosteroids [73], and cholic acid [74]. Most of the induction studies were performed in mice, rats, and other animal models, and DMET protein induction in humans remains largely unexplored.…”
Section: Enzyme Inductionmentioning
confidence: 99%